2006
DOI: 10.11646/zootaxa.1178.1.1
|View full text |Cite
|
Sign up to set email alerts
|

A checklist of the butterflies of Melanesia, Micronesia, Polynesia and some adjacent areas

Abstract: A systematic checklist of the butterflies of Melanesia, Micronesia and Polynesia is presented. A significant number of previously unpublished island records were found in major museum collections in the UK, Australia and the USA. Aspects of butterfly distribution, authorship of names, and taxonomy are addressed, and sources for about 2,200 published butterfly names are incorporated in a comprehensive bibliography of Pacific butterflies. Combined with recent publications dealing with specific areas, such as Pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 1 publication
2
31
0
Order By: Relevance
“…The second author has encountered this species widely, notably in the Solomon Islands (Tennent, 2002), Vanuatu (Tennent, 2009), and the islands of Milne Bay Province, Papua New Guinea (ongoing fieldwork). Tennent (2006) also collated numerous records for the Pacific. Parsons (1998: 615) states that villida is 'apparently absent from Timor, the Lesser Sunda Islands and the Moluccas', but, as will be seen from the following list, this is not the case.…”
Section: Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…The second author has encountered this species widely, notably in the Solomon Islands (Tennent, 2002), Vanuatu (Tennent, 2009), and the islands of Milne Bay Province, Papua New Guinea (ongoing fieldwork). Tennent (2006) also collated numerous records for the Pacific. Parsons (1998: 615) states that villida is 'apparently absent from Timor, the Lesser Sunda Islands and the Moluccas', but, as will be seen from the following list, this is not the case.…”
Section: Distributionmentioning
confidence: 99%
“…1 Barnett & Emms, 1998]); Cocos (Keeling) Islands (West Island [Holloway, 1983], Direction Island [= Tikus or Rat Island]); Christmas Island [Indian Ocean; Pendlebury, 1932]; Java [material seen with specific locality data is all from eastern Java]; Raäs [Kalis, 1933] [Chernov, 1994;Tennent, pers. ob., 2010]); Sudest; Solomons Archipelago (Bougainville, Alu, Maleai, Fauro, Mono, Choiseul, Vella Lavella, Ranongga, Ghizo, Kolombangara, New Georgia, Rendova, Santa Isabel, Pavuvu, Marulaon, Mane, Mbanika, Bellona, Rennell, Guadalcanal, Savo, Florida, Malaita, San Cristobal, Nendo, Utupua, Reefs, Tikopia, Anuta, Pio [Chernov, 1994]); Australia, including many small offshore islands [Smithers & Butler, 1983;Powell, 1998;Williams & Powell, 1999, 2006Edwards et al, 2001] [Chernov, 1994]); Society Islands (Tahiti); Tuamotu (Makatea, Tepoto, Napuka, Moruroa, Marutea South, Maria, Hikueru, Makemo); Gambier (Temoe); Marquesas [Fruhstorfer, 1912: 522; but see below].…”
Section: Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Hirowatari 1992) recognised 57 species and additional species have been described by Tennent and Rawlins (2012), and Takanami (1994). From approximately west to east, Kunte et al (2015), Corbet and Pendlebury (1993), Treadaway and Schröder (2012), Rawlins et al (2014), Parsons (1998), Tennent (2002) and Tennent (2006) identified six species for India, 16 for the Malay Peninsula, 16 for the Philippines, 21 for Maluku, 15 for Papua New Guinea, eight for the Solomon Islands and nine for the remainder of the South West Pacific, respectively.…”
Section: Introductionmentioning
confidence: 99%